Wang Bing's filmmaking of the China dream : narratives, witnesses and marginal spaces - Pollacchi, Elena (Critical Asian cinemas., 2021)
This volume offers an organic discussion of Wang Bing's filmmaking across China's marginal spaces and against the backdrop of the state-sanctioned 'China Dream'. Wang's work has contemporary China as its focus and testifies to the country's contradictions, not dissimilar to those of contemporary societies dealing with issues of inequality, labour, and migration. 0Without being an activist, Wang Bing gives voice to the subaltern. His internationally awarded documentaries are recognized as world masterpieces. His unique aesthetics bears references to film masters, therefore this investigation goes beyond the divide between Western and non-Western film traditions. 0Each chapter takes a different articulation of space (spaces of labour, spaces of history, spaces of memory) as its entry point bringing together film and documentary studies, Chinese studies, and studies in globalization issues. This volume benefits from the author's extensive conversation with Wang Bing and from insider's observations of film production and the film festival circuit.